The influence of sport-field properties on muscle-recruitment patterns and metabolic response - Hales, M. E.; Johnson II, J. D. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To investigate different sport-field properties` influence on muscle-recruitment patterns and metabolic response during a series of running and agility drills. Methods: Eleven male athletes were fitted with a standard multipurpose training shoe. The test protocol consisting of 4 high-intensity trials with 60-s rests between trials performed on 2 fields with different properties. Time-dependent field properties were measured using the American Standards for Testing and Materials protocol (F-1936). A 30-m pretest and posttest sprint determined fatigue and player performance. Electromyography (EMG) recorded muscle activity for vastus medialis, biceps femoris, gastrocnemius medial head, and tibialis anterior, and metabolic activity analyzed maximal oxygen consumption, heart rate, respiratory exchange ratio, metabolic equivalent, and energy expenditure. Results: A difference was calculated for muscle activity across trials (P = .01) for both surfaces. Muscle activity was <13% on the field with less energy return (P = .01). Metabolic components (maximal oxygen consumption, heart rate, respiratory exchange ratio, metabolic equivalent, and energy expenditure) were significantly different across trials (P = .01) but not significantly different between fields. The participants completed the agility course (5.2%) faster on the field with greater energy return, while caloric expenditure was similar between fields. Conclusions: The findings indicate that field mechanical properties influence muscle-activation patterns. The field demonstrating the greatest magnitude of energy return produces the lowest sprint and agility course times; however, performing on a field exhibiting unfamiliar mechanical properties could cause the athlete to produce atypical movement patterns that might contribute to overuse of the neuromuscular system.